Atypical Diffusion-Restricted Lesion in 5-Fluorouracil Encephalopathy - Lee, W.-W.; Kim, J.-S.; Son, K.R.; Kwon, H.-M. (American Journal of Neuroradiology, 2012)
SUMMARY: Central nervous system toxicity of 5-FU could show various manifestations, such as decreased alertness, disorientation, and agitation. It is generally accepted that lesions of 5-FU encephalopathy are mainly in the deep cerebral white matter and corpus callosum on MR imaging. Here we describe a case of 5-FU encephalopathy in gastric cancer with an atypical reversible diffusion-restricted lesion on MR imaging, showing bilateral basal ganglia, thalami, and parasagittal frontal cortex involvement on diffusion and T2-weighted imaging. BUNblood urea nitrogenCRFchronic renal failureDPDdihydropyrimidine dehydrogenase5-FU5-fluorouracilPT/INRprothrombin time/international normalized ratio